Primary hepatic leiomyosarcoma concurrent with early-stage lung adenocarcinoma: a rare case report - Peng, Weizhong; Xiao, Xiaohui; Li, Lu; Yu, Yi (Frontiers in Oncology, 2025)
Primary hepatic leiomyosarcoma (PHL) is an extremely rare malignant mesenchymal tumor, accounting for less than 2% of all primary hepatic malignancies. We report a case of a 46-year-old female who presented with a one-year history of abdominal distension and pain. Imaging revealed a 6×5×4 cm mass in the left hepatic lobe (segments 3/4) and incidentally detected a suspicious pulmonary nodule. Laparoscopic partial left hepatectomy followed by thoracoscopic wedge resection of the left upper lung confirmed the diagnoses of primary hepatic leiomyosarcoma and primary lung adenocarcinoma (cT1aN0M0), respectively. This case highlights the importance of comprehensive diagnostics, immunohistochemical analysis, and multidisciplinary management of rare hepatic tumors, particularly when concurrent malignancies are present. This first reported case of concurrent PHL and primary lung adenocarcinoma provides valuable insights for clinical practice in managing patients with rare hepatic malignancies.